PERANCANGAN SISTEM INFORMASI PENYEWAAN ALAT KESEHATAN PT XYZ BERBASIS WEB - Muhammad Fachriza Pulungan; Hari Purwanto (Fakultas Ilmu Komputer dan Desain - Unsurya, 2023)
We know medical device are very important for the world of health, various forms and uses. One example of and important medical device for humans is the Cath-Lab and CT-Scan, Wich are tools intended for heart sugery and various other medical uses. These tools are priced quite expensive so that not a few hospitals can have these tools. PT XYZ or it can be abbreviated as PT. XYZ is a company that sells these medical devices, because with the high cost of the tool PT. XYZ has difficulty selling it to hospitals in need because of the high coast that must be incurred by the hospital, therefore the author wants to make a solution for PT. XYZ so that hospitals can easily get Cath-Lab and CT-Scan is by renting it out to every hospital that needs it.Â Keywords: Rental, Waterfall, PHP, MySQL, WEB.